ANALISA DAMPAK VOLTAGE SAG AKIBAT MASUKNYA SMELTER PADA JARINGAN TRANSMISI DI KABUPATEN BULUKUMBA DENGAN PEMODELAN SIMULASI KOMPUTER - Muhammad Rais (Fakultas Teknik Universitas Muhammadiyah Makassar, 2020)
Short duration under voltage or what is known as voltage sag or dip voltage is a decrease in the amount of supply followed by a recovery after a short period of time of failure. Referring to the IEEE 1159-1995 standard, the voltage dip is defined as the rms voltage drop of 10% - 90% for the amplitude value for 0.5 cycles to less than one minute. This study aims to determine an overview of the switching effect of the smelter in the 150 kV high voltage overhead line system (SUTT) in the South Sulawesi electrical system. The results of the analysis with the help of ATP software show that the sulsel system is still in a safe condition because the voltage drop and magnitude that occur are still within tolerance limits.